SCSBRS126 Dueto: irrigated rice variety resilient to cold and heat at reproductive stage - Marschalek R. (2023)
© 2023, Brazilian Society of Plant Breeding. All rights reserved.SCSBRS126 Dueto is a late-maturing high yield performing cultivar released by Epagri/Embrapa/Udesc. It has high tillering capacity, but poor resistance to lodging, medium resistance to blast, with long, slender grains and good sensory/cooking traits, and it has lower sterility under cold stress at microsporogenesis/anthesis and under heat at anthesis.